Características en la producción del habla en niños de 6 a 7 años con frenillo lingual alterado de la IE Liceo Naval "Almirante Guise". - Fajardo Perry, Nora Ynés (Pontificia Universidad Católica del Perú, 2014)
The following is a simple descriptive study, whose main objective is to determine the features in speech production in children aged 6 to 7 with a lingual frenulum alteration.